Neuropatia periférica em ruminantes: estudo retrospectivo - Moreira, Juliana Junqueira [UNESP]; Olivo, Giovane [UNESP]; Delfiol, Diego José Zanzarini [UNESP]; Borges, Alexandre Secorun [UNESP]; Gonçalves, Roberto Calderon [UNESP]; Amorim, Rogério Martins [UNESP]; Chiacchio, Simone Biagio [UNESP] (My University, 2011)
Peripheral neuropathies consist of injury or loss of peripheral nerves function, observed by conscious proprioceptive deficits, hypoalgesia or analgesia and hyporeflexia or areflexia of the affected limb. The nerve damage can be of three types: neuropraxia, axonotmesis or neurotmesis, and can be caused by trauma, inflammation, compression, stretch and rupture of muscle fibers. The type of injury determines if recovery will be total or parcial; however, treatment is expensive and slow, making euthanasia necessary in many times. This retrospective study selected 14 animals with peripheral injury, being eight bovine, six sheep and any goat, from 562 ruminants submitted to the Large Animal Internal Medicine. Race, age, sex, evolution time, clinical signs, probable cause, treatment and recovery were evaluated. The radial nerve injury and brachial plexus was observed in 9 of the 14 animals evaluated, resulting in a morbidity rate of 64.3% in ruminants, being 42.85% in cattle and 21.43% in sheep. The other 5 (35,7%) animals had obturator and sciatic nerve damage. The incidence rate for the group of sheep was 50% and 75% for the group of cattle. The efficacy of recommended treatment using analgesia, vitamin E (tocopherol) and B1 (thiamine), suspension aided by lifting system, massage and electrotherapy was evidenced by the recovery rate of 71.43%.
Peripheral neuropathy in ruminants: a retrospective study
Keywords: Paresis; Neurology; Peripheral nerves; Cattle; Sheep; Paresia; Neurologia; Nervos periféricos; Bovinos; Ovinos